Laboratory findings that occur in Klebsiella pneumoniae blood stream infection in HIV-infected children compared to HIV uninfected children, at a South African children's hospital, Cape Town, 2006–2011: a nested-descriptive cross-sectional study - Shapaka, Johanna Tekla (Department of Paediatrics and Child Health, 2023)
Background: Bloodstream infection (BSI) caused by Klebsiella pneumoniae (KP), is a leading cause of hospitalassociated childhood mortality. There are limited data on how poor outcomes of KPBSI can be predicted in poorly resourced areas. This study aimed to assess if the profile of differential counts from full blood counts (FBC) taken at two time points in children <13 years with KPBSI could be used to predict the risk of death. Methods We conducted a retrospective study of a cohort of children admitted to hospital between 2006-2011 with KPBSI. FBC collected within 48 hours (T1) of blood culture and 5-14 days later (T2), were reviewed. Differential counts were classified as abnormal if they were higher or lower than laboratory ranges for normal results. The risk of death was assessed for each category of differential counts. Risk ratios adjusted (aRR) for potential confounders were used to estimate the effect of cell counts on risk of death using multivariable analysis. Data were stratified by HIV status. Results: Of 296 children included, median age 5 (IQR:2-13) months, 82 were HIV -infected. Ninety-five (32%) of the children with KPBSI died. Mortality in HIV-infected and uninfected children was 39/82 (48%) and 56/214 (26%), respectively (p <0.001). Independent associations with mortality were observed with leucopenia, neutropenia and thrombocytopenia. Risk of mortality in children with thrombocytopenia at T1 and T2 was aRR 2.5 (95% CI: 1.34-4.64) and 3.18 (95% CI: 1.31-7.73) respectively in the HIV-uninfected group, whereas the risk for mortality in the HIV-infected group with thrombocytopaenia at T1 and T2 was aRR 1.99 (95% CI: 0.94-4.19) and 2.01 (95% CI: 0.65-5.99) respectively. Neutropenia in the HIV-uninfected group at T1 and T2, showed aRR 2.17 (95% CI: 1.22- 3.88) and 3.70 (95% CI 1.30-10.51) respectively, while in the HIV-infected group, they were aRR 1.18 (95% CI 0.69-2.03) and 2.05 (0.87-4.85) at similar time points. Risk of mortality related to leucopenia at T2 was associated with mortality in HIV-uninfected and HIV-infected patients was aRR 3.22 (95%CI 1.22-8.51) and 2.34 (1.09-5.04) respectively. Persistently high band cell percentage at T2 in HIVinfected children indicated a risk of mortality of aRR 2.91 (95% CI 1.20-7.06). Conclusion Abnormal neutrophil counts and thrombocytopenia are independently associated with significant mortality in children with KPBSI. In resource-limited countries haematological markers have the potential to predict KPBSI mortality.